PENGARUH POSISI KEUANGAN, LABA RUGI, PERUBAHAN EKUITAS DAN ARUS KAS TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR AGRICULTURE YANG TERCATAT DI BEI PERIODE 2017 – 2019 - Chairil Anwar (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This study aims to determine: (1) Effect of Financial Position on Stock Returns for 2017-2019 period, (2) Effect of Profit and Loss on Stock Returns for 2017-2019 period, (3) Effect of Changes in Equity on Stock Returns for 2017-2019 period, (4) Effect of Cash Flow on Stock Returns for 2017-2019 period, (5) Effect of Financial Position, Profit and Loss, Changes in Equity and Cash Flow simultaneously on Stock Returns for 2017-2019 period. The data in this study are secondary data obtained from the annual financial statements of agriculture sector companies in the Indonesian Stock Exchange (IDX). This type of research is quantitative research. This research was conducted using a sample of 16 companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Data analysis techniques used are descriptive statistics, classic assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination tests. Based on hypothesis testing using the t test, it was concluded that the Financial Position, Profit and Loss, Changes in Equity and Cash Flow did not have a significant effect on Stock Return partially. Based on the F test it was concluded that the Financial Position, Profit and Loss, Changes in Equity and Cash Flow did not significantly influence the Stock Return simultaneously.